Blood flow distribution in hind limb bones and joint cartilage from young growing pigs. - Nakano, T (1986)
Blood flow distribution was studied in hind limb bones and joint cartilage from four ten week old and four 20 week old pigs using 141Ce-microspheres. In general, blood flow rate was greater in the epiphyseal and metaphyseal cancellous bone than in the cortical bone and joint cartilage. In the epiphyseal cancellous bone, blood flow rate was three to tenfold greater (P less than 0.01) in the surface 2 mm layer than in the remaining deeper bone in all femoral and tibial samples examined. In the joint cartilage, blood flow rate in the femoral condyle was greater (P less than 0.05) than in the proximal femur, patella, central tarsus and metatarsus in ten week old pigs, and was greater (P less than 0.05) in the femoral condyle than in the patella and metatarsus in 20 week old pigs. A significant (P less than 0.05) age-associated decrease in the rate of blood flow was observed in the femoral, patellar and metatarsal cartilage. Within the femoral condyle, no differences in blood flow were found between areas associated with relatively high versus relatively low incidences of osteochondrosis.